From Benzofurans to Indoles: Palladium‐Catalyzed Reductive Ring‐Opening and Closure via β‐Phenoxide Elimination. Issue 1 (26th November 2018) - Perego, Luca A.; Wagschal, Simon; Grüber, Raymond; Fleurat‐Lessard, Paul; El Kaïm, Laurent; Grimaud, Laurence
Abstract: Benzofurans can undergo ring‐opening by a palladium‐catalyzed process resulting in C−O bond breaking. Benzofuran‐tethered 2‐iodoanilines give synthetically interesting 2‐(3‐indolylmethyl)phenols in an overall reductive process. Mechanistic studies suggest that this unusual reaction proceeds by carbopalladation of benzofuran giving a 3‐palladated 2, 3‐dihydrobenzofuran intermediate, which then fragments by an uncommon trans ‐elimination of the phenoxide group β to the metal. In this transformation, N, N ‐diisopropylethylamine (DIPEA) acts as a base and as a reducing agent: it regenerates palladium(0) from palladium(II), thus allowing catalytic turnover. Abstract :